Ecological assessment on the forest productivity after enrichment planting in degraded secondary forest in inikea degraded forest rehabilitation site - Looi, Kok Chuong (2020)
A study on the ecological assessment on the forest productivity after enrichment planting in degraded secondary forest in INIKEA Degraded Forest Rehabilitation site. The objectives of the study were as following: (1) to document the remnant dipterocarp species composition and distribution, (2) to evaluate soil physicochemical properties, (3) to determine leaf litterfall pattern and its species composition; and ( 4) to document litter arthropod communities across the three phases rehabilitation program and a non-rehabilitated site. All the samplings were conducted in the ten plots set-up in a 30m radius across the study site, with nine plots representing a rehabilitation phase and one planting technique, while a last single plot left for the control site. A total of 83 dipterocarp trees were recorded and representing 23 species from five dominant genera found in the Sabah. F-statistic value proving the Model 1 (Dipterocarp species number) and Model 2 (Dipterocarp species abundance) are significant enough to reject the null hypotheses due to the value larger than 1.0, but p-value indicating these models are almost significant instead. In term of assessment in soil physicochemical properties, the soils of all ten plots was moderately acidic with subsurface horizon more acidic than surface horizon. The concentration of remaining soil variables were mostly higher in surface soil horizon than subsurface soil horizon. PERMANOVA and PERMDISP have proved that only the 'Phase' category of both soil horizons was affected by both location and dispersion effects; the remaining groups were affected only by location effect. Kruskal-Wallis H test indicated proved that Ca, P, DN, Mg, and Zn of surface soil horizon and all the 13 variables of subsurface soil horizon were statistically significant. Of RDA triplots of both surface and subsurface soil horizon, the arrows belonged to biplot variable of subsurface soil horizon is more segregated than the surface soil horizon, and variable pH is seem to play central role in controlling the availability of exchangeable elements for nutrient cycles. In term of plant litterfall, the plots belonged to Gapcluster plantings were generally contributed more litterfall than that of Line planting and Liberation treated plots. Also, plots of Phase 1 generally produced more plant litterfall than that of Phase 2, Phase 3 and Control plots. Dipterocarp is the major plant family to contribute approximate 30% in most of the plots. Jaccard similarity index was indicating that Plln has highly similar vegetation communities with Liberation plots, while P2Ln has a high similarity index with the Control plot. In terms of leaf litterfall nutrient content, variables such as TC, Ca, Fe, Mg, and Mn are proved to statistically significant variables by Kruskal-Wallis Index at p-value below 0.05. PERMANOVA and PERMDISP index have shown nutrient content of 'Plot,' and 'Planting Technique' categories are affected by location effect and clear distinction between the clusters of Line and Gap-cluster plantings with the cluster of liberation treated and non-rehabilitated plots. On the other hand, a total of 4850 individual of arthropods was collected across the ten plots. The largest proportion of arthropods were collected in P3Ln. Arthropod from order Hymenoptera is the most abundant samples from all the samplings. According to Kruskal-Wallis test with alpha level set below 0.1, arthropod orders, namely Araneae, Blattodea, Coleoptera, Diplopoda, and Pseudoscorpiones are indicated to be statistically significant variables. Based on RDA plot, Blattodea, Diplopoda and Coleoptera could play major roles as 'litter transformer' and 'ecosystem engineer' in influencing the flow of soil nutrient elements in nutrient cycle and soil fertility as the explanatory variables, namely P, Mg, Mn, pH and BD are correlated with the said arthropod orders. The result of this study could be used as fundamental data on the effects of enrichment plantings and liberation treatment in rehabilitating the degraded secondary rainforest, despite only was conducted in microcosm scale.